2016
DOI: 10.1016/j.theriogenology.2016.04.077
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine methylation of sperm DNA in horse semen after cryopreservation

Abstract: Semen processing may contribute to epigenetic changes in spermatozoa. We have therefore addressed changes in sperm DNA cytosine methylation induced by cryopreservation of stallion semen. The relative amount of 5-methylcytosine relative to the genomic cytosine content of sperm DNA was analyzed by ELISA. In experiment 1, raw semen (n = 6 stallions, one ejaculate each) was shock-frozen. Postthaw semen motility and membrane integrity were completely absent, whereas DNA methylation was similar in raw (0.4 ± 0.2%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 34 publications
3
42
2
Order By: Relevance
“…Cryopreservation may also directly affect the epigenome of the paternal DNA; recent studies have shown that cryopreservation increases the level of DNA methylation in equine sperm [10] and the expression of genes important to intracellular regulation of epigenetic status [37]. Notably, we also found significant reduction in abundance of transcripts for histones in CRYO embryos.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Cryopreservation may also directly affect the epigenome of the paternal DNA; recent studies have shown that cryopreservation increases the level of DNA methylation in equine sperm [10] and the expression of genes important to intracellular regulation of epigenetic status [37]. Notably, we also found significant reduction in abundance of transcripts for histones in CRYO embryos.…”
Section: Discussionsupporting
confidence: 59%
“…Exploration of differentially-expressed genes at the molecular and cellular level revealed alterations in important functions including ATP synthesis, regulation of transcription, nucleosome assembly, chromatin silencing, protein synthesis, and redox regulation. Alterations in these genes help to explain the reduced fertility observed with cryopreserved sperm attributable to increased early embryo mortality [9, 10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the effects of some commonly used techniques has still not been evaluated. Very recently, for example, Aurich, Schreiner, Ille, Alvarenga, and Scarlet () showed that semen freezing increased DNA methylation in horses, whatever the cryopreservative solution used. Finally, new techniques are constantly being developed such as in vitro maturation of human oocytes, ooctyte freezing, cytoplasmic or pronuclear transfer and these need to be evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Processing of semen for cryopreservation was carried out at room temperature (20°C) as described before (Aurich, Schreiner, Ille, Alvarenga, & Scarlet, 2016). The sperm pellet was partially resuspended in the remaining supernatant and split into three aliquots each diluted at a 1:1 ratio with the three cryopreservation extenders, respectively.…”
Section: Cryopreservation and Thawing Of Semenmentioning
confidence: 99%